Brønsted acid cocatalysis in photocatalytic intramolecular coupling of tertiary amines: efficient synthesis of 2-arylindols. Issue 31 (19th July 2016) - Yuan, Xiaoqian; Wu, Xinxin; Dong, Shupeng; Wu, Guibing; Ye, Jinxing
Abstract : We report herein a highly efficient intramolecular coupling reaction of tertiary amines and ketones (α, β-unsaturated ketones) by using a Brønsted acid as a cocatalyst, affording 2-arylindols in good to excellent yields (up to 92%) under visible light irradiation at room temperature. Abstract : We report herein a highly efficient intramolecular coupling reaction of tertiary amines and ketones (α, β-unsaturated ketones) by using a Brønsted acid as a cocatalyst, affording 2-arylindols in good to excellent yields (up to 92%) under visible light irradiation at room temperature.